Reka Cipta Salaka Sebagai Upaya Akselerasi Ekonomi Masyarakat Prasejahtera Di Desa Hargobinangun - Al Ghifary, Dzaffrin; Rachmadina, Farizka Zahra; Nuraini, Afridha; Meliala, Rana Nurul Anisa Nabil Syah Ali; Raqi, Muhammad; Amalia, Dzakira Fitri; Zahro, Qonitah Fathimah; Salsabila, Kayla Azzahrah; Bara, Putri Florensia; Rizki, Nurfaiz Muhamad; Gunawan, Indra; Setyana, Nafiah Rahma; Wahyono, Tri (Universitas Muhammadiyah Yogyakarta, 2025)
Hargobinangun Village in Sleman Regency has an area of 184.2 hectares of snake fruit plantations. This shows great potential in snake fruit management. However, the village community still faces economic challenges due to the low selling price of snake fruit, lack of snake fruit processing innovation, and limited access to market products. In addition, the high unemployment rate and the community's dependence on government assistance are the main problems that hinder economic growth in Hargobinangun Village. Based on this, the service program carried out focuses on processing innovative products made from snake fruit, ranging from snake fruit skin tea, snake fruit seed coffee, and snake fruit jam. This program aims to improve the knowledge and skills of the people of Hargobinangung village in processing snake fruit. This program involves community groups such as KWT Ngestimakmur, PKK Wonorejo-Ponggol, and Karang Taruna GMWP (Wonorejo Ponggol Youth Generation). The methods used include socialization, skills training, and product innovation workshops. In addition, we also train target communities in the field of product marketing through the use of digital media, including e-commerce and social media platforms, to expand market reach. The results of the program implementation show that there is an increase in people's understanding and skills in processing snake fruit, as well as confidence in marketing products. The positive impact obtained is the strengthening of collaboration between community groups so as to support the creation of a local entrepreneurial ecosystem. Through this success, Hargobinangun Village is expected to be able to develop into an entrepreneur-based independent village with salak processed innovation products as a superior product identity. This empowerment strategy shows that optimizing local potential can be an effective solution to improve people's welfare and encourage sustainable economic growth.